Measures Taken by Governments to Mitigate the Effects of the COVID-19 Pandemic: Indirect Financial Support to Business - Kanapickienė, Rasa; Keliuotytė-Staniulėnienė, Greta; Teresienė, Deimantė; Budrienė, Daiva; Valukonis, Mantas (Buhalterinės apskaitos teorija ir praktika, 2021)
The COVID-19 pandemic crisis differs in nature from the previous financial crisis and therefore different solutions must be taken. In this context, governments are seeking to help businesses deal with the effects of the pandemic, which have had the greatest impact on corporate liquidity. The analysis of government support measures in the context of the COVID-19 pandemic has shown that EU governments use not only direct but also indirect financial support to business. However, the latter is not sufficiently analysed in scientific works. The aim of the study is to analyse the measures of indirect financial support for business applied by EU governments and to provide the classification of the measures described. In order to achieve the aim, the following methods of scientific research were used: analysis, synthesis, induction, deduction, abstraction, and analogy of scientific literature, normative documents, reports and reviews of international organisations, and support measures applied in governments’ practice. The study developed an original structure of government indirect financial support measures for business, comprising three components of government support measures: (1) minimisation of legal norms related to corporate finance; (2) indirect financial assistance related to labour law; (3) strengthening the legal framework for corporate finance. The measures analysed are described in more detail by distinguishing them into separate groups. The structure developed is based on concrete examples of application in EU countries and could contribute to a more targeted approach to business support in the future.